Attention-deficit hyperactivity disorder in adults: A guide for the general practitioner - G.I. van Schalkwyk; J. Schronen (South African Family Practice)
Attention-deficit hyperactivity disorder (ADHD) has an estimated prevalence of 3.5% in adults. Knowledge regarding the diagnosis and treatment of this condition remains limited amongst general practitioners. The clinical presentation is highly variable, and the manifestations of the characteristic symptoms of inattention, hyperactivity and impulsivity are different in adults. Furthermore, there is a high incidence of comorbidity. At present, no definitive criteria are available for making the diagnosis. Several rating scales are available, but the diagnosis is essentially a clinical one, and can often only be made with the help of a psychiatrist. Essential features include the presence of ADHD in childhood and significant functional impairment as an adult. Core ADHD symptoms do not always form part of the presenting clinical picture, and awareness of some of the more common initial complaints is important. Stimulants have been shown to be an effective treatment for this condition in both children and adults. ADHD is a rapidly evolving field, and the optimum tools for diagnosis and treatment are not yet available. A functional knowledge of this condition is essential for the general practitioner.